1973
DOI: 10.1159/000240550
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thyroxine on the Maturation of Fetal Rabbit Lungs

Abstract: The effect of thyroxine on the development of fetal rabbit lungs was evaluated. In the first series of experiments involving 26 animals, thyroxine was given intramuscularly to pregnant does for two days prior to premature delivery of fetuses at 26 to 28 days gestation (full term: 30 days). There was no evidence of accelerated lung maturation in the fetuses treated with thyroxine. In a second series of experiments of 20 pregnant does, thyroxine was injected directly into the fetuses and amniotic sacs in one ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
2
1

Year Published

1974
1974
1991
1991

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(63 citation statements)
references
References 0 publications
3
57
2
1
Order By: Relevance
“…One approach is by intraamniotic instillation of T3 and T4. Experimentally, direct in utero administration of thyroxine to fetal rabbits results in enhanced lung maturation as judged by lung lavage surfactant content and morphometric studies (37)(38)(39). The second approach, stimulating endogenous fetal production of T3 and T4 by maternal treatment with TRH (which does cross the placenta), is the approach that is currently being tested clinically.-This recent clinical interest in testing the efficacy of prenatal TRH treatment in turn stimulated us to investigate the effects of TRH on both fetal lung biochemical development and newborn lung adaptation to hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is by intraamniotic instillation of T3 and T4. Experimentally, direct in utero administration of thyroxine to fetal rabbits results in enhanced lung maturation as judged by lung lavage surfactant content and morphometric studies (37)(38)(39). The second approach, stimulating endogenous fetal production of T3 and T4 by maternal treatment with TRH (which does cross the placenta), is the approach that is currently being tested clinically.-This recent clinical interest in testing the efficacy of prenatal TRH treatment in turn stimulated us to investigate the effects of TRH on both fetal lung biochemical development and newborn lung adaptation to hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Since glucocorticoids are not completely effective in preventing respiratory distress syndrome in human infants (1), there was current interest in the use of other agents (2). Several studies have indicated that thyroid hormones have similar influences on lung differentiation (3,4). Effects of glucocorticoids and thyroid hormones were more than additive (9, suggesting different mechanisms of actions.…”
mentioning
confidence: 99%
“…These findings were subsequently substantiated by numerous studies on various species. A similar effect on fetal lung maturation has also been demonstrated for several other hormones: adrenocorticotropic hormone (46), thyrotropin releasing hormone (42), thyroxine (44,52), 17pestradiol (39), and prolactin (20). Animal experiments and clinical observations suggest that Badrenergic agonists, such as isoxsuprine (24) and hexoprenaline (28), and cholinergic agonists, such as oxotremorine (I), also promote fetal lung maturation.…”
mentioning
confidence: 55%